Ethidium bromide-bridged mesoporous silica hybrid nanocarriers for fluorescence cell imaging and drug delivery applications. (26th October 2021) - Santhamoorthy, Madhappan; Thirupathi, Kokila; Periyasamy, Thirukumaran; Thirumalai, Dinakaran; Ramkumar, Vanaraj; Kim, Seong-Cheol
Abstract : We report the fabrication of mesoporous organosilica hybrid nanocarriers with red-fluorescence behaviour under UV-light for pH-responsive drug delivery and red-fluorescence-based bioimaging applications in cancer therapy. Abstract : Mesoporous silica nanocarriers with dual/multifunctionalities are thought to be good candidates for dual/multimodal applications such as combined drug delivery and bioimaging. In this study, new red fluorescent organosilica materials were conveniently produced with diurea-ethidium bromide (DU-EB) functional units integrated in the pore wall framework for simultaneous diagnosis and therapy. We found that the prepared mesoporous silica hybrid nanocarrier system exhibited strong red fluorescence under UV-light (365 nm) while retaining excellent photo- and chemical-stability. The integrated ethidium bromide functional units in the mesopore walls cause the red fluorescence. By loading/releasing doxorubicin (Dox)/5-fluorouracil (5-FU) as a model cargo, the synthesized DU-EB@MSH materials were tested at various pH levels (pH 5.0, 6.2 and 7.4), and the cytocompatibility of the red-fluorescent DU-EB@MSH nanocarrier system was assessed using human breast cancer (MCF-7) cells. The experimental results revealed that the drug release behavior is primarily determined by the pH of the intracellular medium, and red-fluorescence was induced by a UV-light (365 nm) trigger. All the study results suggested that the DU-EB@MSH drug carrier system could be useful for red-fluorescence bioimaging and chemotherapeutic applications in cancer therapy.